Information intervention and farmers’ green technology adoption: evidence from perspective of risk perception - Suyun Chen; Suyun Chen; Xinfeng Zhu; Wentai Bi; Zongze Li; Hengyun Ma (Frontiers in Sustainable Food Systems)
The adoption of green technology by farmers contributes to the green transformation of agricultural production. It is also crucial for ensuring the safety of agricultural products, and protecting the ecological environment. Based on a survey sample of 213 households in Henan province and using a difference-in-differences model, we investigate the effect of an information intervention on farmers’ green technology adoption. We find that the information intervention significantly promotes farmers’ green technology adoption. We also find that the information intervention changes farmers’ income risk perception, safety risk perception and health risk perception. Furthermore, the effect of the information intervention on green technology adoption is more pronounced for farmers with high information literacy and social learning than for those with low information literacy and social learning. Our finding reveals the mechanism by which information interventions influence farmers’ green technology adoption and provides some policy implications for green agricultural development from the perspective of information interventions.